Penerimaan Panelis Serta Analisis Usaha Mi Instan Berbasis Jagung Lokal Pelalawan dan Tapioka - Dira, Debby Martha; Pato, Usman; Rifai, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purposes of this study were to analyze the level of acceptance by the panelists and to analyze the business feasibility of instant noodles made from Pelalawan local corn flour and tapioca. The research was conducted experimentally by making instant noodles from local corn flour and tapioca and then tested for panelists acceptance and business analysis. Data of panelists acceptance were analysis by Cochran’s Q test at the level of 5%. Test results show that Cochran's Q indicates the number of 5.455 which means H0 accepted with the understanding that the instant noodles made from local corn flour and tapioca were accepted by the panelists. Business analysis of instant noodles made from Pelalawan local corn flour and tapioca show that HPP values ​​obtained by the total cost were Rp. 1,268.05 and HPP from main total variable cost were Rp. 1,206.69. Profit obtained was Rp 221,048.37/20 kg of main raw materials. Business efficiency with RCR of 1.58. BEP based on the amount of production value were 191.48 and the BEP based on  production price were Rp. 1,268.05 with economic value were Rp. 239,580. Keywords : Pelalawan local corn, tapioca, instant noodles, panelist acceptance, business analysis.